Agricultural Supply Management and Market Power: Evidence from the U.S. Dairy and Potato Industries. Issue 4 (28th September 2016) - Bolotova, Yuliya V.
ABSTRACT: Agricultural over‐supply, increasing output price volatility, and producers' returns below production costs were the economic forces that influenced the decision of the organizations of agricultural producers in the U.S. dairy and potato industries to implement agricultural supply management programs. Using a theoretical framework, this research evaluates potential seller market power of agricultural cooperatives implementing agricultural supply management practices at the farm‐gate level. A theoretical analysis is conducted by comparing agricultural cooperatives with classic cartels. Available empirical evidence on the effects of agricultural supply management programs in the U.S. dairy and potato industries is discussed. [EconLit citations: L1, L2, Q13].